Self-Enhancement and the Medial Prefrontal Cortex: The Convergence of Clinical and Experimental Findings - Saeed Yasin; Anjel Fierst; Harper Keenan; Amelia Knapp; Katrina Gallione; Tessa Westlund; Sydney Kirschner; Sahana Vaidya; Christina Qiu; Audrey Rougebec; Elodie Morss; Jack Lebiedzinski; et al. (Brain Sciences, 2022)
Self-enhancement (SE) is often overlooked as a fundamental cognitive ability mediated via the Prefrontal Cortex (PFC). Here, we present research that establishes the relationship between the PFC, SE, and the potential evolved beneficial mechanisms. Specifically, we believe there is now enough evidence to speculate that SE exists to provide significant benefits and should be considered a normal aspect of the self. Whatever the metabolic or social cost, the upside of SE is great enough that it is a core and fundamental psychological construct. Furthermore, though entirely theoretical, we suggest that a critical reason the PFC has evolved so significantly in Homo sapiens is to, in part, sustain SE. We, therefore, elaborate on its proximate and ultimate mechanisms.